2010
DOI: 10.1155/2010/612315
|View full text |Cite
|
Sign up to set email alerts
|

48XXYY Syndrome in an Adult with Type 2 Diabetes Mellitus, Unilateral Renal Aplasia, and Pigmentary Retinitis

Abstract: A 45-year-old male was referred for diabetes mellitus. Clinical examination found a family history of multiple precocious deaths, strong consanguinity, personal history of seizures during childhood, small testicles, small penis, sparse body hair, long arms and legs, dysmorphic features, mental retardation, dysarthria, tremor, and mild gait ataxia. Investigations found pigmentary retinitis, metabolic syndrome, unilateral renal aplasia, and hypergonadotropic hypogonadism, and ruled out mitochondrial cytopathy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…However, while tall stature was reported in 48,XXYY syndrome [7], it also concluded that patients with 48,XXYY syndrome were mostly of short stature, which is in accordance with our patient, who was not tall [2]. It was reported that patients with this syndrome suffered from infertility [14] due to its association with hypergonadotropic hypogonadism [3,15] as well as its association with other endocrine manifestations such as acromegaloidism [16]. In our study, this concurred with our clinical findings, and our patient's presenting symptom of infertility, which were suggestive for our patient to undertake genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, while tall stature was reported in 48,XXYY syndrome [7], it also concluded that patients with 48,XXYY syndrome were mostly of short stature, which is in accordance with our patient, who was not tall [2]. It was reported that patients with this syndrome suffered from infertility [14] due to its association with hypergonadotropic hypogonadism [3,15] as well as its association with other endocrine manifestations such as acromegaloidism [16]. In our study, this concurred with our clinical findings, and our patient's presenting symptom of infertility, which were suggestive for our patient to undertake genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…A slight malrotation of the right kidney was also determined. Previous cases with renal aplasia and ectopy were described in 48,XXYY males; however, cross ectopy and malrotation of the kidney in 48,XXYY/47,XYY patients have not been reported in the literature yet [ 5 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case of 48,XXYY syndrome with unilateral renal aplasia has been previously reported. [ 8 ] He has had impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%